Effect of mother in development of nutritional education for her children (Journal of the College of Education for Women, 2019)
Reprehensible during the period of human life ,particular in child hood and after weaningbaby,analmeating habits have acquired his remaining life time and here high Iights,the role ofthe mother in the childs education,dietar habits, and health methods and what is beneficial tohis health and in sufficien quantities for the baby .brooze trails are learned by the childin thehome with animportant and significant role in the future,inacht.aaralgame course wisely,afterbecoming more in dependent in its delision-making an choices beyond the control of parents.The present study aimed to message measure the awareness of food the mother and her role inthe development of food awareness sons, and its relation ship with some variable in come,years of experience (marriage),the number of family members nominalism .(family size),academic achievement).Achieve the objective of the study was built (scale tool)to measure the awareness of food forthe mother and setting its assumptions,the question naire was adopted in the preparation of thefood ,for information on study was conducted aprospective study in cluded 50 families wereselected randomly of Baghdad on both sides of Karkh and Rusafa this question naire included an openquestion.Q\what is food culture ,and are there steps that must.Be followed to raise awareness .the scale was preparing after it was prestented to the expertsto ascertain the extent coverage of the prographscontainted in the measure for food awarenessand to ensure the validity of prographs and non-life and also to make sure of discriminatorypower ,which guaranteed the scale sample has been tested after arranging.Desecendinggrades,ldentified(27%)of the total bases that received the highesgrad andrepresent (54)family and its ration (27%)and represent families (54).Set the foundation on which got lowergrades on ascale of awareness .the arithmetic mean wasextracted and indication of dergres .the binary value extracted,it turns out that statisticallysignificant differences of the level(0.05).According to the stability of the scale and using the correlatic coefficient ,the correlationcoefficient (73%)which is a good reliablity coefficient and then the final application of thescale used in this study the following statistic message test second (choice second)correlationcoefficient bresson,(coefficient AlFA KARAN BAK).The second test of one sample and A analysis variance.Findings Search:1-NO statistically significant difference in the scale of food awareness to mother for variablemothiy in come.2-they were statistically significant differences in the scale of food awareness to mother forvariable number of years of marriag.(experience ,the differences for the sake category(15-11).3-NO satistically significant differences to mother for variable (number of family members).4-NO satistically significant differences to mother for variable (Academicachievement).